-4x 3y 2(7xy 4)

Question

Asked 6/4/2013 6:44:48 AM

Updated 5/30/2014 9:05:24 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/30/2014 9:03:35 AM]

s

jeifunk|Points 9870|

jeifunk|Points 9870|

jeifunk|Points 9870|

Shey091808|Points 863|

sunny4691|Points 1084|

jeifunk|Points 9870|

bongche|Points 3864|

stan_r|Points 1382|

shiela098|Points 205|

shiela098|Points 205|

Question

Asked 6/4/2013 6:44:48 AM

Updated 5/30/2014 9:05:24 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/30/2014 9:03:35 AM]

Rating

3

-4x^3y^2(7xy^4) = -28x^4y^6

Added 5/30/2014 9:03:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:05:51 AM]

3

1/4(8m - 4n) +1/3 (6m + 3n)

= 2m - n + 2m + n

= 4m

= 2m - n + 2m + n

= 4m

Added 5/30/2014 9:04:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:06:44 AM]

3

-y(2y^3 - 8) = -2y^4 + 8y

Added 5/30/2014 9:05:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:07:03 AM]

Simplify -3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3). Select the answer in descending powers of p.
1 - 7p- 2p2+ 5p3
5p3- 2p2- 7p+ 1
1 + 7p+ 2p2- 5p3
-5p3+ 2p2+ 7p+ 1 **Weegy:** The answer is 1 - 7p- 2p2+ 5p3. **User:** Identify the polynomial.
x3y3
monomial
binomial
trinomial **Weegy:** The answer is c.trinomial ; In elementary algebra, a trinomial is a polynomial consisting of three terms . **User:** Find the sum of the given polynomials.
5m + 2n, n - 3m, and 7 - 3n
7 - 2m
2m+ 7
14m+ 5n- 6
9m **Weegy:** (b)2m+ 7 **User:** Simplify 5t + (t - 3) - [(7t + 5) - (8 - 3t)].
-4t
4t
-10t
10t **Weegy:** (a)-4t is the answer. 5t + (t - 3) - [(7t + 5) - (8 - 3t)] = -4t **User:** Find the sum of the given polynomials.
ax + by + c, 2ax - 3by + c, and by - c
3ax-by+c
3a+x-bc
3ax+by-cd
bx- 3bc+a **Weegy:** the answer should have been 3ax-2by+c. The closest among the choices is letter a **User:** Take 4a - 3b + 2c from 2a - 3b + 4c.
-2a + 2c
-2a - 2c
2a + 2c
2a - 2c **Weegy:** 2a-2c **User:** Take 2y2 - 3y - 5 from y3 - 6y2 + 5y. Select the correct answer.
y3- 2y2+ 3y+ 5
y3- 4y2+ 2y- 5
y3- 4y2+ 2y+ 5
y3- 8y2+ 8y+ 5 **Weegy:** (y^(3)-6y^(2)+5y)-(2y^(2)-3y-5)
Multiply -1 by each term inside the parentheses.
y^(3)-6y^(2)+5y+-2y^(2)+3y+5
Since -6y^(2) and -2y^(2) are like terms, [ subtract 2y^(2) from -6y^(2) to get -8y^(2).
y^(3)-8y^(2)+5y+3y+5
Since 5y and 3y are like terms, add 3y to 5y to get 8y.|||
|||
y^(3)-8y^(2)+8y+5 is the answer. ] **User:** Subtract -2k3 + k2 - 9 from 5k3 - 3k + 7.
3k3+ k2- 3k - 2
-7k3+ k2+ 3k - 16
7k3- k2- 3k + 16 **Weegy:** The answer is 7 k^3+k^2-3 k-2 **User:** (x2 + 4)(x2 - 4)
**Weegy:** x+3)(x-3) = x2+3x-3x -9 = x2-9 **User:** Select the correct product.
(6 - d)(d2 - 5 + 3d)
6d2- 30d
d3- 3d2- 23d+ 30
d2+ 2d- 30
-d3+ 3d2+ 23d- 30 **Weegy:** 6d2- 30d d3- 3d **User:** (x2 + 3x + 1)(x2 + x + 2)
**Weegy:** 15x+2. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! **User:** Select the correct product.
(x2 + 4x + 8)(2x - 1)
2x3+ 7x2+ 12x- 8
2x3- 7x2- 12x- 8
x2+ 6x+ 7
x2+ 8x- 8 **Weegy:** The correct answer to the presented problem is (a) 2x3 + 7x2 + 12x - 8 **User:** Select the correct product.
(y + ... (More)

Question

Updated 6/27/2014 5:05:42 PM

9 Answers/Comments

(6 - d)(d^2 - 5 + 3d) = -d^3+ 3d^2+ 23d- 30

Added 6/27/2014 7:10:52 AM

This answer has been confirmed as correct and helpful.

(x2 + 3x + 1)(x2 + x + 2) = x^4 + 4x^3 + 6x^2 + 7x + 2

Added 6/27/2014 7:14:39 AM

This answer has been confirmed as correct and helpful.

(y + z)3

=(y)(3)+(z)(3)

=3y+ 3z

=(y)(3)+(z)(3)

=3y+ 3z

Added 6/27/2014 7:15:54 AM

This answer has been flagged as incorrect.

Flagged by yeswey [6/27/2014 5:05:17 PM]

Subtract -2k3 + k2 - 9 from 5k3 - 3k + 7 :

(5k3 - 3k + 7) - (-2k3 + k2 - 9) = 7k3- k2 -3k+16

(5k3 - 3k + 7) - (-2k3 + k2 - 9) = 7k3- k2 -3k+16

Added 6/27/2014 7:17:56 AM

This answer has been confirmed as correct and helpful.

Find the product mentally.
(2j + 7)(2j - 7)
4j2+ 49
4j2- 49
2j2- 28j- 49 **Weegy:** If you mean (r - s)^2, then the product is r^2-2rs+s^2. If you mean (r - s) x 2, then the product is 2r - 2s. **User:** (2j + 7)(2j - 7) **Weegy:** If you mean (r - s)^2, then the product is r^2-2rs+s^2. If you mean (r - s) x 2, then the product is 2r - 2s. **User:** Select the correct product.
(a + 8)(b + 3)
ab+ 8a+ 3b+ 24
ab+ 3a+ 8b+ 24
11ab
24ab **Weegy:** ab+3a+8b+24 is the answer. **User:** Select the correct product.
(2x + 9)(x + 1)
2x2+ 11x+ 9
3x2+ 11x+ 9
2x2- 7x+ 9
2x2+ 11x+ 10 **Weegy:** Can you clarify your question please? **User:** Select the correct product. (2x + 9)(x + 1) **Weegy:** Simplifying
4(2x + 1) = 3(x + 8)
Reorder the terms:
4(1 + 2x) = 3(x + 8)
(1 * 4 + 2x * 4) = 3(x + 8)
(4 + 8x) = 3(x + 8)
Reorder the terms:
4 + 8x = 3(8 + x)
4 + 8x = (8 * 3 + x * 3)
4 + 8x = (24 + 3x)
Solving
4 + 8x = 24 + 3x
Solving for [ variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
4 + 8x + -3x = 24 + 3x + -3x
Combine like terms: 8x + -3x = 5x
4 + 5x = 24 + 3x + -3x
Combine like terms: 3x + -3x = 0
4 + 5x = 24 + 0
4 + 5x = 24
Add '-4' to each side of the equation.
4 + -4 + 5x = 24 + -4
Combine like terms: 4 + -4 = 0
0 + 5x = 24 + -4
5x = 24 + -4
Combine like terms: 24 + -4 = 20
5x = 20
Divide each side by '5'.
x = 4
Simplifying
x = 4
source: ] **User:** Select the correct product.
(j + 7)(k - 5)
-35jk
jk- 12jk- 35
jk- 5j+ 7k- 35
7j- 5k (More)

Question

Updated 5/26/2014 11:55:09 PM

3 Answers/Comments

(2j + 7)(2j - 7) = 4j^2 - 49

Added 5/26/2014 11:53:55 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 11:55:30 PM]

(2x + 9)(x + 1)

= 2x^2 + 2x + 9x + 9

= 2x^2 + 11x + 9

= 2x^2 + 2x + 9x + 9

= 2x^2 + 11x + 9

Added 5/26/2014 11:54:34 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 11:56:06 PM]

Simplify 8 + 3{x - 2[x + 5(x + 3)]}.
-33x + 82
33x - 82
-33x - 82 **Weegy:** (c)-33x - 82 is the answer.
**User:** Find the product.
-7(8 + k)
-56 + 7k
-7k - 56
-7k + 56 **Weegy:** The correct answer is (b) -7k - 56 **User:** Find the product.
3(m + n)
3m + n
3m + 3n
3mn **Weegy:** 3(m + n) =b.3m + 3n **User:** a^5· a^7 **Weegy:** ?7 + 5 = -2 **User:** a^5* a^7
**Weegy:** ?7 + 5 = -2 **User:** a^5x a^7 **Weegy:** 5x2+3=13 **User:** Find the sum of 5m + 3n + p, -5p + 3n, and 2n - m.
-4m + 8n - 4p
4m + 8n + 4p
4m - 8n - 4p
4m + 8n - 4p **Weegy:** Answer is 4m + 8n - 4p.
**User:** Identify the polynomial.
x3- y3 + z
monomial
binomial
trinomial **Weegy:** The answer is c.trinomial ; In elementary algebra, a trinomial is a polynomial consisting of three terms . **User:** Simplify (2n + 5) - (3n + 7) + (4n - 9).
-3n - 11
3n - 11
-3n + 11
3n + 11 **Weegy:** Simplify (2n + 5) - (3n + 7) + (4n - 9).
ANSWER: 3n - 11
**User:** Find the sum of 2x2 + 3x - 4, 8 - 3x, and -5x2 + 2.
-3x2- 2
-7x2- 2
-3x2+ 6
-7x2- 6x- 2 **Weegy:** -18x2-6x+4 **User:** 2x2 + 3x - 4, 8 - 3x, and -5x2 + 2. **User:** Using the polynomials Q = 3x2 + 5x - 2, R = 2 - x2, and S = 2x + 5, perform the indicated operation.
Q - [R + S]
2x2+ 3x- 9
4x2- 3x+ 9
2x2- 3x+ 9
4x2+ 3x- 9 **Weegy:** D. 5x - 4 is the answer. **User:** Find -x + 10 less than 0.
0
-x + 10
x - 10 **Weegy:** Let x^(1/3) = u ? x^(2/3) = u?
Substitute into equation and solve for u
? 3u? + u - 2 = 0
? 3u? + u - 2 = 0
? 3u? + 3u - 2u - 2 = 0
? 3u (u+1) - 2 (u+1) = 0
? (3u - 2) (u+1) = 0
? (3u - 2) = 0 or (u + 1) = 0 ?? u = 2/3 or -1
From original [ substitution x^(1/3) = u
? x^(1/3) = u
? x = u?
? x = (2/3)? or (-1)?
? x = 8/27 or -1 ] **User:** Simplify a - {b - [c - (d - e) - f] - g}.
a + b + c - d + e - f + g
a - b + c - d + e - f + g
a + b + c + d + e - f + g
a - b + c - d + e + f - g **Weegy:** The correct response to this problem is answer (d) a - b + c - d + e + f - g **User:** Simplify -3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3). Select the answer in descending powers of p.
1 - 7p- 2p2+ 5p3
5p3- 2p2- 7p+ 1
1 + 7p+ 2p2- ... (More)

Question

Updated 7/9/2014 11:18:08 AM

1 Answer/Comment

a^5· a^7 = a^12

Added 7/9/2014 11:18:08 AM

This answer has been confirmed as correct and helpful.

32,020,350

questions answered

There are no comments.